Enhancing Bioproducts in Seaweeds via Sustainable Aquaculture: Antioxidant and Sun-Protection Compounds - Yehoshua Ashkenazi, Doron; López-Figueroa, Félix; Korbee-Peinado, Nathalie; García-Sánchez, Marta; Vega Sánchez, Julia; Ben-Valid, Shoshana; Paz, Guy; Salomon, Eitan; Israel, Álvaro; Abelson, Avigdor (IOAP-MDPI, 2022)
Marine macroalgae are considered an untapped source of healthy natural metabolites and their market demand is rapidly increasing. Intertidal macroalgae present chemical defense mechanisms that enable them to thrive under changing environmental conditions. These intracellular chemicals include compounds that can be used for human benefit. The aim of this study was to test cultivation protocols that direct seaweed metabolic responses to enhance the production of target antioxidant and photoprotective biomaterials. We present an original integrated multi-trophic aquaculture (IMTA) design, based on a two-phase cultivation plan, in which three seaweed species were initially fed by fish effluents, and subsequently exposed to various abiotic stresses, namely, high irradiance, nutrient starvation, and high salinity. The combined effect of the IMTA’s high nutrient concentrations and/or followed by the abiotic stressors enhanced the seaweeds’ content of mycosporine-like amino acids (MAAs) by 2.3-fold, phenolic compounds by 1.4-fold, and their antioxidant capacity by 1.8-fold. The Sun Protection Factor (SPF) rose by 2.7-fold, and the chlorophyll and phycobiliprotein synthesis was stimulated dramatically by an order of magnitude. Our integrated cultivation system design offers a sustainable approach, with the potential to be adopted by emerging industries for food and health applications
Keywords: Algas; Seaweeds; Integrated aquaculture; Mycosporine-like amino acids; Phenolic compounds; Pigments; Antioxidants; Sun protection factor; Bioproducts; Ulva; Gracilaria